Single-cell profiling of lineage determining transcription factors in antigen-specific CD4(+) T cells reveals unexpected complexity in recall responses during immune reconstitution - Phetsouphanh, Chansavath (Immunol Cell Biol, 2017)
Recent studies of protein and gene expression at the single-cell level have revealed that the memory T-cell compartment is more heterogeneous than previously acknowledged. Identifying different T helper subsets involved in memory responses at the single-cell level is thus necessary to understand the level of heterogeneity within this population. Antigen-specific CD4(+) T cells were measured using the CD25/OX40 assay together with a qualitative multiplex single-cell RT-PCR assay. Transcription profiles and subset proportions within the antigen-specific CD4(+) T-cell population were dissected. Cytomegalovirus (CMV)-specific CD4(+) T-cell responses skewed toward a Th1 response, whereas Tetanus toxoid responses skewed toward a Th2 type response. Fluctuations in CD4(+) T-cell subsets were observed within the HIV-Gag-specific response during ongoing antiretroviral therapy. Strong effector responses (Th1) were observed in early treatment, however with ongoing therapy this effector response significantly decreased in combination with an increase in Tregs and circulating Tfh-like BCL-6(+) memory cells. The apparent increase in Tcm in peripheral blood after a several weeks of antiretroviral therapy may be due to Tfh-like cell egress from germinal centers into the periphery.